MENINGKATKAN KETERAMPILAN METAKOGNITIF MELALUI LAYANAN KLASIKAL MULTIMODAL LITERASI SISWA KELAS XI SMA NEGERI 1 AIR PUTIH TAHUN AJARAN 2025/2026 - Abdillah Saputra Sinaga; Rosmala Dewi (STKIP Subang, 2026)
Low metacognitive skills among students result in suboptimal abilities to plan,monitor, and evaluate the learning process. This study aims to enhance students'metacognitive skills through multimodal literacy-based classroom guidance servicesfor Grade XI students at SMA Negeri 1 Air Putih during the 2025/2026 academicyear. The study employs the Guidance and Counseling Action Research (PTBK)method using the Kemmis and McTaggart model, conducted over two cyclescomprising planning, implementation, observation, and reflection stages. Theresearch subjects consisted of 21 students selected based on screening resultsindicating low metacognitive skills. Data collection involved Likert-scalequestionnaires, observation, and documentation, while data analysis utilizeddescriptive quantitative techniques (percentages and categorization) and qualitativeanalysis (data reduction, data presentation, and conclusion drawing). The resultsindicate that prior to the intervention, 21 students (65.62%) fell into the lowmetacognitive skills category. Following the implementation of multimodal literacy-based classroom guidance services, the percentage of students reaching the highcategory increased from 28.5% in Cycle I to 85.7% in Cycle II; meanwhile, theaverage score rose from 56.71 in the pre-cycle stage to 66.33 in Cycle I and 83.67 inCycle II. These findings demonstrate that multimodal literacy-based classroomguidance services are effective in improving students' metacognitive skills,particularly regarding the aspects of planning, monitoring, and evaluating.